Analisis Faktor Pemilihan Karier sebagai Akuntan Publik oleh Mahasiswa Akuntansi di Indonesia Menggunakan Pendekatan Theory of Reasoned Action Model - Duri, Rafika; Helmy, Herlina (Universitas Negeri Padang, 2025)
This research intends to examines the impact of personal interest, financial rewards, parental influence and peer on career choices as public accountants by accounting students in Indonesia. The population of this study was S1 students majoring in accounting in Indonesia who have taken auditing courses. The sample in this research was 385 samples. This type of research is survey research with a quantitative approach. The source of data in this research is primary data. Data collection techniques with questionnaires distributed to students. Data analysis using multiple linear regression analysis. The results show that personal interest, financial rewards, and peer have a positive influence on career choices as public accountants by accounting students in Indonesia. However, parental influence has a negative effect on career choices as public accountants by accounting students in Indonesia.